2005
DOI: 10.1073/pnas.0409818102
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of protein kinase CK2 prevents the progression of glomerulonephritis

Abstract: Glomerulonephritis (GN) is a progressive inflammation that may be caused by a variety of underlying disorders. It is the primary cause of chronic renal failure and end-stage renal disease, which require dialysis and transplantation worldwide. Immunosuppressive therapy has been used to treat GN clinically, but this treatment has had insufficient therapeutic effects. Here, we show that protein kinase CK2 is a key molecule in the progression of GN. cDNA microarray analysis identified CK2␣, the catalytic subunit o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 30 publications
4
50
1
Order By: Relevance
“…5) In the same study, we observed that administration of either antisense oligodeoxynucleotide against CK2α or low molecular weight CK2 inhibitors effectively prevented the progression of renal dysfunction. Based on this background, we focused on developing novel CK2 inhibitors as a therapeutic agent for GN.…”
supporting
confidence: 50%
See 3 more Smart Citations
“…5) In the same study, we observed that administration of either antisense oligodeoxynucleotide against CK2α or low molecular weight CK2 inhibitors effectively prevented the progression of renal dysfunction. Based on this background, we focused on developing novel CK2 inhibitors as a therapeutic agent for GN.…”
supporting
confidence: 50%
“…Since we have demonstrated that administration of CK2 inhibitors ameliorated the progression of GN, 5) we examined the in vivo effects of compound 13 on experimental GN. As with our previous study, 5) WKY rats were injected with anti-GBM antibodies to induce experimental anti-GBM GN.…”
Section: Compound 13 Suppresses the Progression Of Anti-gbm Gn In Vivomentioning
confidence: 99%
See 2 more Smart Citations
“…All cells, growing at a cell density of 5 · 10 5 cells mL -1 , were treated with or without 100 nmol L -1 DEX or 400 nmol L -1 PRD for 24 h. At 0 or 24 h total RNA isolated from each sample was reversetranscribed using the Quantitect reverse transcription kit (Qiagen, Valencia, CA, USA) and this was analyzed by quantitative PCR using ABsolute QPCR SYBR Green Mixes (ABgene, Surrey, UK) in a DNA Engine Opticon2 System (Biorad, Hercules, CA, USA) as described previously (Yamada et al 2005). GAPDH was used to standardize the mRNA levels of target genes.…”
Section: Qrt-pcrmentioning
confidence: 99%